2012
DOI: 10.5915/44-1-10463
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of congenital anomaly rates at birth in Fallujah, Iraq, 2010

Abstract: ObjectivesTo examine numbers of congenital anomaly (CA) at birth overall and by class in one clinic in Fallujah General Hospital, Fallujah, Iraq.Study Design:All congenital anomaly birth referrals to one pediatric clinician at Fallujah General Hospital for an eleven month period beginning November 1, 2009 were recorded. This clinic was one of three clinics to which cases would be referred.Results:There were 291 CA cases registered at birth in the period at the study’s clinic. The total number of births recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 13 publications
(15 reference statements)
3
13
0
Order By: Relevance
“…The high concentrations of uranium in the scalp hair from the Fallujah subjects could not be attributed to either the soil or the water concentrations of uranium. -… these results support the belief that the effects in Fallujah follow the development of a uranium-based weapon or weapons of some unknown type‖ [86]. However, a subsequent review of the literature on congenital abnormalities in Iraq concluded, -As no [sic] enough data on pre 1991 Gulf War prevalence of birth defects in Iraq are not available, the ranges of birth defects reported in the reviewed studies from Iraq most probably do not provide a clear indication of a possible environmental exposure including DU or other teratogenic agents although the country has faced several environmental challenges since 1980‖ [87].…”
Section: Collateral Injuriessupporting
confidence: 77%
“…The high concentrations of uranium in the scalp hair from the Fallujah subjects could not be attributed to either the soil or the water concentrations of uranium. -… these results support the belief that the effects in Fallujah follow the development of a uranium-based weapon or weapons of some unknown type‖ [86]. However, a subsequent review of the literature on congenital abnormalities in Iraq concluded, -As no [sic] enough data on pre 1991 Gulf War prevalence of birth defects in Iraq are not available, the ranges of birth defects reported in the reviewed studies from Iraq most probably do not provide a clear indication of a possible environmental exposure including DU or other teratogenic agents although the country has faced several environmental challenges since 1980‖ [87].…”
Section: Collateral Injuriessupporting
confidence: 77%
“…In the last decade of the 20th century and continuing in the present one, intense military operations on wide geographic extensions have been taking place. From some of the affected countries, medical personnel reported an increase in negative birth outcomes [1][2][3][4][5] and in non-communicable diseases, including cancers, and similar news arrived from shooting grounds and retired military [6,7]. It is known that weaponry contributes to the deterioration of the environment causing acute events of pollution with cancerogenic and teratogenic substances; chronic contamination of the post-war areas by chemicals stable in time in the environment occurs and these are under scrutiny for the relevance for health of heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…Anectodal reports indicated increasing incidence of birth defects in the years following US attacks in 2004 which proved to be due to irradiation 5,6,7,8 . The health system.…”
Section: Discussionmentioning
confidence: 99%